Coconut Palms on the Edge of the Desert: Genetic Diversity of Cocos nucifera L. in Oman - Perera, Lalith; Baudouin, Luc; Bourdeix, Roland; Fadhil, Anwar Bait; Hountondji, Fabien C. C.; Al-Shanfari, Abdulaziz (International Coconut Community, 2011)
In the Gulf region, coconuts are almost exclusively produced from palms growing in the Sultanate of Oman, particularly in the extreme south-eastern coastal plain of the Dhofar Governorate, and specifically within the city limits of Salalah, between the Jebel and the sea. The importance of these coconuts is not only agricultural; historically, the Dhofar palms provided the basic materials to build boats for fishermen and traders on, around and eventually beyond the Indian Ocean. Coconut palms are now one of the main symbols of Salalah city and play a role in both the tourist industry and urban landscaping. In early 2009, twenty-nine sites, representing Oman coconuts on beaches and cultivated lands were chosen from the Dhofar region. COGENT descriptors and DNA analysis were used for the purpose of identifying coconut germplasm available in Oman. The presence was confirmed of varieties that were imported during the 1980s, such as Yellow Dwarf, Green Dwarf and King coconut from Sri Lanka, as well as Malayan Yellow Dwarf and F1 hybrids. The local Oman Tall has the same phenotypic characteristics as other coconuts of South Asia, East and West Africa, the Caribbean and the Atlantic coast of South America. Microsatellite markers, however, reveal a substantial genetic contribution of the South-East Asian coconuts, at levels that are comparable to those found in the Comoros and Madagascar coconuts. Hypotheses about the ancestry of the Oman Tall coconuts are discussed; two genepools are indicated, consecutively involving natural selection, dissemination by floating, domestic selection and dispersal by boat.